Determinants of Internal Audit Effectiveness in Nepalese Commercial Banks: An Inferential Analysis - Mishra, Shila; Karki, Soni (Academic Journal of Simara, 2026)
This study empirically investigates determinants of internal audit (IA) effectiveness in Nepalese commercial banks organizational setting, independence, competence, management support, and audit committee existence using inferential statistical methods to assess significant impacts and IIA standards compliance. A cross-sectional survey (n=102 IA professionals; convenience sampling via online questionnaires) yielded descriptive positives (IA effectiveness M=4.81, all variables ≥ 4.40 on 6-point Likert) and multiple regression results (R2=0.405, Adj. R2=0.374, p=0.000). Inferential analysis confirms significant positive drivers: audit committees (β=0.543, p=0.000) and independence (β=0.443, p=0.000), explaining 40.5% variance and aligning with agency theory/ISPPIA 1100 amid NRB Basel III/RBIA reforms (Cohen & Sayag, 2010; Endaya & Hanefah, 2013). Non-significant factors organizational setting (β=-0.215, p=0.097), competence (β=0.031, p=0.775), management support (β=- 0.124, p=0.273) suggest standardized protocols suffice, though 59.5% unexplained variance signals external influences. Theoretical implications refine frameworks, positioning committees/independence as universal in emerging markets. Practical recommendations: Banks prioritize oversight/charters; NRB mandates RBIA benchmarks.